Hubungan Pola Asuh Ibu dengan Status Gizi Balita di Kelurahan Oesapa Kecamatan Kelapa Lima Kota Kupang - Amindro Umbu Rato Baru; Masrida Sinaga; Marselinus Laga Nur (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
The nutritional status of toddlers is an important indicator in determining the quality of children's health and development. Maternal parenting patterns, including aspects of feeding, health care and developmental stimulation, have a significant role in determining a child's nutritional status. This research aims to determine the relationship between maternal parenting patterns and the nutritional status of toddlers in Oesapa Village, Kelapa Lima District, Kupang City. This type of research is an analytical survey with a cross-sectional design. The population in this study were all mothers with toddlers in Oesapa Village, Kelapa Lima District, Kupang City with a total of 867 people. Sampling was carried out using a simple random sampling technique with a sample size of 87 people. Data was collected through structured interviews using questionnaires, anthropometric measurements of toddlers, and direct observation. The results of data analysis show that there is no significant relationship between feeding practices and the nutritional status of toddlers (p-value = 0.1000), there is a significant relationship between hygiene practices and the nutritional status of toddlers (p-value = 0.050), there is no significant relationship. significant relationship between health care practices and nutritional status of toddlers (p-value = 0.262). It is hoped that the community will use the results of this research as input for efforts to prevent toddler nutritional problems by improving mothers' parenting patterns for toddlers such as types of food and increasing knowledge about toddler nutritional needs in order to avoid toddler nutritional problems.